2013
DOI: 10.4314/ahs.v13i2.2
|View full text |Cite
|
Sign up to set email alerts
|

Nodding syndrome in Mundri county, South Sudan: Environmental, nutritional and infectious factors

Abstract: Background: Nodding Syndrome is a seizure disorder of children in Mundri County, Western Equatoria, South Sudan. The disorder is reported to be spreading in South Sudan and northern Uganda. Results: Nodding Syndrome was associated with Onchocerca volvulus and Mansonella perstans infections, with food use of a variety of sorghum (serena) introduced as part of an emergency relief program, and was inversely associated with a history of measles infection. There was no evidence to suggest exposure to a manmade neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 79 publications
4
82
0
2
Order By: Relevance
“…Exposure to warfare chemicals is readily posited but dismissed as highly improbable given the known neurotoxic properties of such substances, none of which causes repetitive head nodding from atonic seizures, let alone a progressive seizure disorder. Sudanese communities affected heavily by NS also experienced war and displacement but reported no symptoms consistent with neurotoxic exposures when questioned in 2002 9. Moreover, Tanzanian children with signs consistent with NS acquired the brain disease in the absence of war or civil conflict 19.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to warfare chemicals is readily posited but dismissed as highly improbable given the known neurotoxic properties of such substances, none of which causes repetitive head nodding from atonic seizures, let alone a progressive seizure disorder. Sudanese communities affected heavily by NS also experienced war and displacement but reported no symptoms consistent with neurotoxic exposures when questioned in 2002 9. Moreover, Tanzanian children with signs consistent with NS acquired the brain disease in the absence of war or civil conflict 19.…”
Section: Resultsmentioning
confidence: 99%
“…The association in some cases between head nodding and food/eating as a precipitating factor 6 has been noted in another epilepsy-prone population with high prevalence of onchocerciasis, 2 and the possible role of certain plant and fungal neurotoxins in Nodding Syndrome has been discussed. 3 Genetic factors in kifafa have been considered previously 15 but parents of children with Nodding Syndrome were usually free of epilepsy, and familial association of disease can also arise from common exposures to etiologic agents. Febrile convulsions were an antecedent event for amesinzia kichwa in up to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study carried out in 2002 in then-southern Sudan found a positive case association with two parasitic nematodes (Onchocerca volvulus, Mansonella perstans) and an inverse association with childhood measles infection. Among non-infectious environmental exposures, food contamination with fungal neurotoxins could not be excluded 2,3 . Others have suggested without evidence an etiologic role for heavy metals, pesticides, or warfare chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of possible causes were examined with case-control studies in South Sudan 33,34 and northern Uganda 6 including nutritional factors, possible environmental toxins, numerous infections (viral, bacterial, parasitic), and some genetic factors. As a common result of these studies, an association was found between onchocerciasis and NS whereas results on other possible factors were negative or inconsistent.…”
Section: Discussionmentioning
confidence: 99%